Influenza A virus M1 blocks the classical complement pathway through interacting with C1qA - Zhang, Junjie; Li, Gang; Liu, Xiaoling; Wang, Zengfu; Liu, Wenjun; Ye, Xin (Journal of General Virology, 2009)
The matrix (M1) protein of influenza A virus is a conserved multifunctional protein that plays essential roles in regulating the viral life cycle. This study demonstrated that M1 is able to interact with complement C1qA and plays an important inhibitory function in the classical complement pathway. The N-terminal domain of M1 protein was required for its binding to the globular region of C1qA. As a consequence, M1 blocked the interaction between C1qA and heat-aggregated IgG in vitro and inhibited haemolysis. It was shown that M1 protein prevented the complement-mediated neutralization of influenza virus in vitro. In addition, studies on mice indicated that the administration of M1 could promote a higher virus propagation rate in lung and shortened survival of mice infected with the virus. Taken together, these results suggest strongly that the M1 protein plays a critical role in protecting influenza virus from the host innate immune system.